Capabilities of digestate utilization - Marciniak, Aneta (Studia Ecologiae et Bioethicae, 2014)
Currently, there is no harmonized approach across the EU to categorize digestate as a waste or a full-value product. Instruments such as the "End-of-Waste" (EoW) may enable its exclusion from the scope of the Waste Framework Directive. Digestate can be an attractive fertilizer and provide an additional source of income for producers, subsequently eliminating the costs of its disposal. According to current legislation and the status of the market in Poland, digestate is usually treated as a by-product requiring disposal and causing additional outlays for a company. This article presents the valid regulations concerning the possibilities of the agricultural application of digestate.